Fatores que influenciam no sucesso e longevidade do controle das ferrugens da cana-de-açúcar por variedades resistentes - Mistura, Tatiane de Fátima (2016)
Sugar, ethanol and bionergy are products generated from sugarcane, whose current demand remains high. However, two rust diseases have threatened its yield, brown rust (Puccinia melanocephala) and orange rust (P. kuehnii). The most efficient method to control these diseases is resistant varieties. The success and longevity of varieties depends basically on two factors: pathogen diversity and correct evaluation of genotype reaction. Therefore, chapter 1 of this dissertation aimed to examine phenotypic and genotypic diversity of rusts pathogens and existence of a direct correlation between these traits. Genotyping of P. melanocephala employed 31 isolates and 39 for P. kuehnii with 10 SSR markers. The genetic diversity was verified through UPGMA clustering and PCoA analyses. The phenotypic diversity was investigated by leaf lesion area and compatible/incompatible interaction between host and pathogen. Data of this work showed similar grouping between UPGMA and PCoA with identification of nine genetic subpopulations for P. kuehnii and 10 subpopulations for P. melanocephala. As for phenotypic diversity, three races were identified in P. kuehnii whereas two were detected in P. melanocephala. Direct correlation between genetic and phenotypic diversity was only observed in P. kuehnii. The chapter 2 examined reaction of five sugarcane commercial varieties to P. kuehnii over different period of time as well as quantity and viability of urediniospores. For disease progress disease, three isolates were inoculated on five varieties and their reactions evaluated 21, 28, 35, 42 days after by disease score. Disease reaction measured by quantity and viability of uredinispores was examined in two different trials. In the first, spores from different type of lesions were investigated 42 days after inoculation, in the second, spores from the same type of reaction but from a susceptible and resistance varieties were observed. Our data identified one variety which reaction changed over time. Therefore, in order to avoid false resistant materials other traits should be taking into account, quantity and viability of urediniospores.